Peningkatan kemampuan menulis kembali teks nonfiksi melalui penerapan model cooperative integrated reading and composition (circ) pada peserta didik kelas iv sekolah dasar - Yoda Hari Kristiawan; Retno Winarni; Fadhil Purnama Adi (Universitas Sebelas Maret, 2021)
The research purposed to increase the students ability especially in rewriting nonfiksi teks on students class IV SD Negeri 2 Tanduk Ampel Boyolali by Cooperative Integrated Reading and Composition Models. The subject of this research was students class IV SD Negeri 2 Tanduk Ampel Boyolali. They were amounts 26 students. The form of this research was Classroom Action Research within somecycles. The data was collected by test and observation. The test was used to measure the ability of rewriting nonfiksi teks and the observation was used to measure teacher perform and student activity. The data was also analysed by using interactive data analysis.The result showed that Cooperative Integrated Reading and Composition Models was proven able to improve the ability of rewriting nonfiksi teks on students class IV SD Negeri 2 Tanduk Ampel Boyolali. It was proven by the grade average in the first cycle and second cycle always improved. The first cylce was only 11 (42,31%) from 26 students who passed the minimum ≥ 70. The highest grade was 88, the lowest grade was 40, and the grade average was≥ 70 in the first cycle. In the second cyle, the grade increased. Amounts 21 students (80,77%) could pass the test and get grade ≥ 70. The highest grade was 90, the lowest grade was 60, and the grade average was 73,21 in the second cycle.